Tafsir al-Lughawi>>>: Histori dan Penerapannya - m fudz (STIU Al-Mujtama Pamekasan, 2019)
Abstract: This article discusses the tafsir al-lughawi> especially in terms of the aspects of balaghah al-Qur'an. Tafsir al-lughawi> is one of the features of interpretation that explains the verses of the al-Qur’an from the side of language. Because the al-Qur'an has a very high language style, the interpreter who will interpret the al-Qur’an with this style must have the ability in the balaghah of the Qur'an. The seeds of this interpretation have existed since the time of Prophet Muhammad, which was then continued by the next generation. In the following period, the tafsir al-lughawi> was divided into three periods, namely the period of formation, strengthening/rooting, and renewal. Regarding balaghah al-Qur'an, Al-Rummani> in his al-Nukt fi> I’ja>z al-Qur'a>n divides it into ten namely ijaz, tashbi>h, isti’a>rah, tala>’um, fawa>sil, taja>nus, tasri>f, tadmi>n, muba>laghah,and baya>n. Keywords: Tafsir el-Lughawi>, Bala>ghah, el-Rummani